Antiinflammatory and antinociceptive activities of Zingiber zerumbet methanol extract in experimental model systems - Zakaria, Zainul Amiruddin; Tengku Mohamad, Tengku Azam Shah; Chai, Teng Chear; Wong, Y. Y.; Israf Ali, Daud Ahmad; Sulaiman, Mohd Roslan (Karger, 2010)
OBJECTIVE: The present study was carried out to determine the antiinflammatory and antinociceptive activities of a methanol extract of Zingiber zerumbet rhizomes (MEZZ) using various experimental model systems. MATERIALS AND METHODS: The MEZZ was prepared by macerating oven-dried (50 degrees C) powdered rhizomes (1.2 kg) of Z. zerumbet in 80% methanol in a ratio of 1:20 (w/v) for 48 h. The supernatant was collected, filtered and evaporated to dryness under reduced pressure (50 degrees C) yielding approximately 21.0 g of the crude dried extract. The crude dried extract was stored at -20 degrees C prior to use and was dissolved in normal saline (0.9% NaCl) immediately before administration at concentrations required to produce doses of 25, 50 and 100 mg/kg. RESULTS: All dosages of MEZZ showed significant (p < 0.05) antiedema activity when assessed using the carrageenan-induced paw edema test and the cotton-pellet-induced granuloma test. The MEZZ exhibited significant (p < 0.05) antinociceptive activity when assessed by the writhing, hot plate and formalin tests. Pretreatment with naloxone (5 mg/kg) significantly decreased the latency of discomfort produced by the 100 mg/kg dose of MEZZ in the hot plate test. CONCLUSION: MEZZ produced antiinflammatory and antinociceptive activities which may involve the inhibition of bradykinin-, prostaglandin-, histamine- and opioid-mediated processes.